Aspectos zootécnicos e sanitários de propriedades leiteiras do munícipio de Itaperuna (RJ) em 2005 - Luiz Carlos Nolasco Barreto (2007)
The subject of this study is dairy cattle raising in Itaperuna, Northwest region of the state of Rio de Janeiro and the purpose of the exercise is to help the dairy farmers of this part of the country. The research was done with 110 milk producers from a total of 1009 farms for the whole of the municipality. The study was presented in the form of chapters and their contents were considered inseparable of the milk production activity and their causes and effects on the production, productivity and health of the dairy herds. In the first chapter we studied the effects of the herds composition on the milk production, it was observed that there were very few productive animals in the herds. The second chapter dealt with the genetic composition of the herds and their adaptation to the environment. It was conclude that the racial composition of the herds must be altered in order that the farms become more efficient. The third chapter took into consideration the handling of the herds by the farmers and the results in production and productivity. The factors considered relevant were the topography of the farms, rainfall, temperature and feeding of the herds in order to determine the influence of these variables on the milk production both in the rain and the dry season. The performance of the herds was very low; small annual production and productivity per individual cow with consequent low profitability for the land. The four chapter objective was to study the herds health conditions and to compare the use recommended scientific procedures with the actual methods used by the farmers. The conclusion was that success of the dairy activity in the region depends on projects to improve the health conditions of the herds. It was observed that the low profitability of the land and the of the dairy activity is a consequence of the farmers little knowledge of techniques readily available and perfectly adaptable to the region.